2018
DOI: 10.11607/prd.3700
|View full text |Cite
|
Sign up to set email alerts
|

Novel Collagen Matrix to Increase Tissue Thickness Simultaneous with Guided Bone Regeneration and Implant Placement in Esthetic Implant Sites: A Feasibility Study

Abstract: The purpose of this case series was to assess safety and feasibility of a novel resorbable collagen matrix (CMX) to enhance tissue thickness simultaneous with implant placement and guided bone regeneration (GBR) in esthetic sites over an 8-week healing period. Soft tissue thickness at implant sites and adjacent teeth was monitored with an ultrasonic device. Overall tissue contour changes were assessed by sequential digital surface model superimpositions. Periodontal parameters and patient-related outcomes reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Autogenous soft tissue graft procedures, including autogenous free gingival grafts and connective tissue grafts, are used as gold standard methods for soft tissue augmentation. Nevertheless, the disadvantages of autogenous soft tissue grafts include the possibility of volume shrinkage, morbidity, and the limitations of host tissues (Chappuis et al, ). Therefore, soft tissue substitutes, including allogeneic, xenogeneic, or alloplastic soft tissue substitutes, have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Autogenous soft tissue graft procedures, including autogenous free gingival grafts and connective tissue grafts, are used as gold standard methods for soft tissue augmentation. Nevertheless, the disadvantages of autogenous soft tissue grafts include the possibility of volume shrinkage, morbidity, and the limitations of host tissues (Chappuis et al, ). Therefore, soft tissue substitutes, including allogeneic, xenogeneic, or alloplastic soft tissue substitutes, have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Second, behavioral control was difficult in the experimental animals, unlike in human patients who became extremely careful after surgery. In a clinical prospective study, Chappuis and colleagues (2018) [ 32 ] performed simultaneous GBR and soft tissue volume augmentation using volume-stable collagen matrix, leading to 2.1 mm of tissue volume increase. Third, in the present canine study, the maxillary premolar region was chosen as the surgical site.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data on procedures applying an EP protocol estimated that the soft tissue grafting accounted for more than 40% of the overall tissue volume (Schneider et al, 2011). Chappuis et al (2018) found that grafting with VCMX alongside EP (with simultaneous GBR) induced a 1.56‐mm increase in soft tissue thickness after 8 weeks . Another type of collagen matrix was very recently compared with CTG for EP (Schmitt et al, 2021), where CTG led to a larger gain of soft tissue volume compared with using a collagen matrix, with no statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%